Akad Musyarakah Dalam Pembiayaan Perdagangan Dan Pertanian Di Lembaga Keuangan Mikro Agribisnis (LKMA) Syariah Barokah - Mas'ut Mas'ut; Soim Soim (Jurnal Dinamika Ekonomi Syariah, 2020)
Partnership-based products with profit sharing such as Musharaka as the competitive superior product of Islamic banking have not experienced growth like other products. The lack of development of partnership-based products in Islamic banking that is more flexible in terms of term, especially long-term financing, causes Islamic banking to have more of its products based on fixed income financing which is similar to the conventional pattern which uses a fixed income structure and tends to be short term. and medium. At LKMA Syariah Barokah, it has a superior product, namely musyarakah. Musyarakah is a profit sharing contract when two or more entrepreneurs holding funds / capital work together as business partners, financing new or existing business investments. Business partners who own capital are entitled to participate in company management, but it is not mandatory. The parties can divide the work of managing the business according to their agreement and can also ask for salaries / wages for the labor and expertise they devote to the business